SISTEM PAKAR DIAGNOSA PENYAKIT DAN HAMA PADA TANAMAN LADA DENGAN METODE FORWARD CHAINING BERBASIS ANDROID - Deki Prianto; Fauziah Fauziah; Endah Tri Esti Handayani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Pepper Plantation is currently experiencing a significant decline from both the quality as well as the difficult treatment. As for some of the factors affecting the decrease in the form of disease and pests. These problems are difficult to overcome because of the limited number of experts who are able to identify and provide solutions to pepper plants. So it takes an expert system capable to identify diseases and pests as well as handling solutions by leveraging the android-based technology using forward chaining. This research was conducted using the survey directly into the object of research and interviews to experts. The testing is done by testing the accuracy of data involving 35 reached 97,14%. with the accuracy results prove that the method of forward chaining can work well in the expert system of diagnosis of disease and pest of pepper plants.